Pengaruh Pendidikan Kesehatan Reproduksi dengan Metode Ceramah dan Leaflet Terhadap Pengetahuan Pada Remaja di Madrasah Aliyah Yapim Ngeluk Penawangan Kabupaten Grobogan - Hariyatmoko, Tofa, Dwi Astuti, S.Pd., M.Kes, Yuli Kusumawati, SKM., M. Kes (Epid) (2013)
Knowledge about reproductive health is very important to know for adolescents. This study aimed to determine the effect of reproductive health with education lecture method and leaflets to knowledge in adolescent. This research is a quasi exsperimental design with one group pretest-posttest. The subjects were teenagers who attended the MA YAPIM Ngeluk Penawangan Grobogan district. The population in this study were all students for class X and XI by the number of 106 students, and the total sample of 28 students for each treatment. The sampling technique used was simple random sampling. The statistical analysis used in this study is paired t test. Based on the results of this research note that there is the influence of reproductive health knowledge using the lecture method (p=0,003) and leaflets (p=0,006) for knowledge among adolescents in MA YAPIM Ngeluk Penawangan Grobogan district. There were significant differences between the reproductive health knowledge education given by the method of Lectures and Leaflets (p = 0.000).